LOCAL CULTURE-BASED EDUCATION: CREATING A LEARNING ENVIRONMENT THAT PROMOTES LOCAL INTEGRITY - Eka Sartika; Salam, Trubus Semiaji (Adisam Publisher, 2024)
Local culture-based education represents a learning paradigm that integrates local cultural wisdom and values into educational curricula and practices. The aim of this approach is to create a learning environment that is rooted in the social, cultural, and student environment, thus enriching the learning process with relevant experiences and perspectives. In this study, we explored the benefits of local culture-based education, including strengthening cultural identities, developing skills relevant to local contexts, and increasing community engagement and participation in the educational process. The method of research used is literature by searching for references that match the context of research. Research results show that students who participate in local culture-based education tend to have a greater sense of pride and appreciation for their cultural heritage, which has a positive impact on learning motivation and a sense of attachment to the community. Furthermore, curricula designed to meet local needs and potential encourage the application of skills in authentic settings, enhancing the relevance and applicability of learning. Implementation of local culture-based education also facilitates intercultural dialogue, strengthens tolerance, and encourages intergenerational collaboration, enriching the learning environment and society as a whole.